2018
DOI: 10.1002/ldr.3231
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers' investments in sustainable land management in Burundi: A case‐study in the provinces of Gitega and Muyinga

Abstract: Understanding farmers' decision‐making to tackle land degradation by means of sustainable land management (SLM) practices is essential for policy makers. The main objective of this study was to identify factors that influence farmers' investments in SLM. A survey was conducted in two provinces of Burundi (Gitega and Muyinga) among 160 households. Methods for data analysis comprised descriptive statistics and multinomial logistic regression. It was derived that both provinces experience severe land degradation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The population of Burundi was 8.05 million in 2008, with nearly 90% of people living in rural areas and depending on subsistence agriculture [33]. In most parts of rural Rwanda and Burundi, formal credit does not exist and households rely on informal or semi-formal borrowing from institutions such as micro-finance institutions, cooperatives, NGOs, village savings and loan associations (VSLA) and input suppliers [34,35].The amount of credit borrowed per capita per year in Rwanda is relatively small. On average, it ranges from US$34 for informal sources to US$55 for semi-formal sources.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of Burundi was 8.05 million in 2008, with nearly 90% of people living in rural areas and depending on subsistence agriculture [33]. In most parts of rural Rwanda and Burundi, formal credit does not exist and households rely on informal or semi-formal borrowing from institutions such as micro-finance institutions, cooperatives, NGOs, village savings and loan associations (VSLA) and input suppliers [34,35].The amount of credit borrowed per capita per year in Rwanda is relatively small. On average, it ranges from US$34 for informal sources to US$55 for semi-formal sources.…”
Section: Contextmentioning
confidence: 99%
“…On average, it ranges from US$34 for informal sources to US$55 for semi-formal sources. Some studies in Burundi have reported average credit sizes of US$70.07 from VSLA groups with most of the loans not exceeding US$12.58 [35]. Male-headed households (MHHs) in Rwanda are less credit constrained than female-headed households (FHHs) [34].…”
Section: Contextmentioning
confidence: 99%
“…As of 2013, such measures (progressive terraces and bench terraces) have been implemented over more than 855,114 ha [ 72 ]. Tanzania and Burundi have also implemented SWC measures and have achieved remarkable results [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of farmland and dependence on wood for fuel has pushed deforestation, with forests currently covering only 6.6% of the territory. Erosion rates in the highlands of Burundi can reach 100 tons ha −1 (Ndagijimana, Kessler, & Asseldonk, 2019), aggravated by increasingly more frequent torrential rains. The resulting loss of soil fertility and its effect on food security make better land stewardship by smallholders a top priority in Burundi.…”
Section: Building a Foundation For Sustainable Changementioning
confidence: 99%